2019
DOI: 10.1002/ece3.5591
|View full text |Cite
|
Sign up to set email alerts
|

Mate fidelity in a polygamous shorebird, the snowy plover (Charadrius nivosus)

Abstract: Social monogamy has evolved multiple times and is particularly common in birds. However, it is not well understood why some species live in long‐lasting monogamous partnerships while others change mates between breeding attempts. Here, we investigate mate fidelity in a sequential polygamous shorebird, the snowy plover (Charadrius nivosus), a species in which both males and females may have several breeding attempts within a breeding season with the same or different mates. Using 6 years of data from a well‐mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…For example, arctic bird species have typically short breeding seasons due to the harsh and stochastic environmental conditions, and tend to exhibit high fidelity to a mate, which is likely to improve offspring survival 17 , 18 . In contrast, mild environments in temperate and tropical regions tend to provide a more prolonged breeding season so that an individual might initiate multiple clutches with the same or different mates 1 , 19 , 20 . The influence of environmental conditions on mating decisions has been observed in a variety of taxa including flies, fish, frogs and birds 21 – 23 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, arctic bird species have typically short breeding seasons due to the harsh and stochastic environmental conditions, and tend to exhibit high fidelity to a mate, which is likely to improve offspring survival 17 , 18 . In contrast, mild environments in temperate and tropical regions tend to provide a more prolonged breeding season so that an individual might initiate multiple clutches with the same or different mates 1 , 19 , 20 . The influence of environmental conditions on mating decisions has been observed in a variety of taxa including flies, fish, frogs and birds 21 – 23 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that divorcing and rapidly changing a mate may be favoured by some species in order to make the most out of a restricted time budget (e.g. short life span or short breeding season) 1 , 40 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Previously, we have used subsets of these data to report on a wide variety of topics in organismal biology, including sex ratio variation 12 , population viability 13 , courtship behaviour 14 , incubation behaviour 15 , parental care 16 , ontogeny 17 , chronobiology 18 , camouflage mechanisms 19 , offspring desertion 20 and mating system dynamics 21 . The motivation for making our database open is to provide evolutionary ecologists with an accessible resource that will serve as an important repository for addressing overarching questions in organismal biology and conservation.…”
Section: Background and Summarymentioning
confidence: 99%